Germinação e desenvolvimento in vitro de Cattleya Nobilior RCHB. f. (Orchidaceae), e sua aclimatização por meio do uso de palhada de soja no substrato - Oliveira, Silene Lívia Aires de (Universidade Federal do Tocantins, 2020)
Cattleya nobilior (Orchidaceae) stands out for having peculiar attributes that cause its intense exploitation and can lead to the vulnerability of the species. This threaten can be curbed by the use of in vitro techniques. Thus, the objective of the present study was to evaluate the effects of different culture media on the germination and development of Cattleya nobilior under in vitro conditions and to describe leaf anatomical responses of plants during the acclimatization stage using soybean residues as part of the substrate. The effects of the following culture media on the in vitro germination and protocorm development were assessed: Murashige e Skoog (full- and half-strength), Knudson C, and Vacin e Went. Acclimatization was carried out under laboratory and under shade-house conditions using different proportions of Bioplant and soybean residues as the substrate. Anatomical studies were conducted on the leaves of acclimatized plants. KC was the most suitable culture medium for both germination and initial development of C. nobilior. Regarding the acclimatization phase, it is recommended that a substrate composed of 60% soybean residues and 40% Bioplant be initially used. Upon transfer to shade-house conditions plants should be grown in pots containing a mix of 40% soybean residue and 60% Bioplant. These results indicate that soybean residues can be used as an alternative component of the substrate for the acclimatization of C. nobilior. The leaf anatomical characteristics observed were typical of the genus Cattleya and revealed the presence of structures related to epiphytic plants adapted to water-poor environments.